1999
DOI: 10.1046/j.1365-2672.1999.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the micro‐organisms associated with the fermented bread (khamir) produced from sorghum in Gizan region, Saudi Arabia

Abstract: M .A .A . GA SS E M. 1999. Traditional bread (khamir) was made from sorghum flour of two local varieties, Bayadh and Hamra. The bread was prepared by mixing the sorghum flour with water and spices (onion, garlic, lemon juice and fenugreek) in a 1:0·8 (w/w) ratio and fermented for 24 h at 30°C. Two other fermentations were carried out using an inoculum from the previous fermentation. The micro-organisms were isolated from different plates and identified using different characterization systems. Both total bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 19 publications
2
32
0
2
Order By: Relevance
“…Fifty-nine A. flavus, 35 F. verticillioides, and 3 F. proliferatum isolates, obtained from freshly harvested (10) and stored (130) sorghum grains cultivated in Nova Odessa, São Paulo State, were evaluated. Samples (10 g) were collected monthly, and the grains were ground and homogenized in 90 mL water.…”
Section: Aspergillus and Fusarium Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-nine A. flavus, 35 F. verticillioides, and 3 F. proliferatum isolates, obtained from freshly harvested (10) and stored (130) sorghum grains cultivated in Nova Odessa, São Paulo State, were evaluated. Samples (10 g) were collected monthly, and the grains were ground and homogenized in 90 mL water.…”
Section: Aspergillus and Fusarium Strainsmentioning
confidence: 99%
“…The presence of deteriorative fungi with ability to produce mycotoxin in grains and food represents a great hazard for human and animal health, and it has been reported for sorghum in many countries with a high frequency of Aspergillus and Fusarium genera (1,7,11,10,25).…”
Section: Introductionmentioning
confidence: 99%
“…It can be used in production of fermented and unfermented bread, stiff porridge, thin porridge, steamed c1ooked products, boiled whole or pearled, snack foods, alcoholic beverages, and nonalc1oholic beverages (Rooney and Serna-Saldivar, 1982). The sorghum flour is used to prep1ared local bread known as Khamir in Gizan province, Saudi Arabia (Gassem, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal contamination makes the food unfit for consumption by causing discolouration, loss of nutrients, heating and mustiness (Bhattacharya and Raha, 2002). Fungi, especially those belonging to the genera Aspergillus, Penicillium and Fusarium have been reported to occur in food (Pitt et al, 1994;Gassen, 1999). Surveys conducted worldwide also revealed that Aspergillus species are known to frequently contaminate food and are able to produce mycotoxins such as aflatoxins, which are of serious problem (Wild and Hall, 2000;Achar et al, 2009).…”
Section: Resultsmentioning
confidence: 99%